Soil fungal and bacterial communities reflect differently tundra vegetation state transitions and soil physico-chemical properties - Huusko, K (via Mendeley Data) (2024)
Supplementary data for the manuscript entitled "Soil fungal and bacterial communities reflect differently tundra vegetation state transitions and soil physico-chemical properties", New Phytologist.The excel file contains information of the experimental design, plant, fungal and bacterial communities, soil physico-chemical properties and site associated data. There are 8 sheets in total in the file: the first sheet contains descriptions for data sheets and variables, and other sheets actual data.Sheets:*Description_of_data: Description of data sheets and variables*Experimental_design: Information of the experimental design. *Soil_variables: Site related information of soil physico-chemical variables, extracellular enzyme activities, microbial respiration*Plant_community: Plant community data*ITS2_OTU_table_L7: Fungal species level operational taxonomic units (OTUs) and their sequence counts*ITS2_OTU_taxonomy_functional: Taxonomic and functional information related fungal OTUs*16S_OTU_table_L7: 16S species level operational taxonomic units (OTUs) and their sequence counts*16S_OTU_taxonomy: Taxonomic information related 16S OTUs THIS DATASET IS ARCHIVED AT DANS/EASY, BUT NOT ACCESSIBLE HERE. TO VIEW A LIST OF FILES AND ACCESS THE FILES IN THIS DATASET CLICK ON THE DOI-LINK ABOVE